The Downstream Extension of the Core Sequence of T7 Promoter in NASBA Primer Design: the Impact on Efficacy of Amplification - Khmeleva, S.A.; Vasileva, Y.A.; Ptitsyn, K.G.; Kurbatov, L.K.; Timoshenko, O.S.; Suprun, E.V.; Radko, S.P.; Lisitsa, A.V. (Biomedical Chemistry: Research and Methods, 2026)
NASBA (Nucleic Acid Sequence Based Amplification) is a method of isothermal RNA amplification with a potential for laboratory and on-site detection of infectious agents. The method relies on the presence of the T7 RNA promoter in one of NASBA primers and NASBA efficacy depends to a large extent on the promoter strength. In in vitro transcription, the promoter strength is known to markedly depend on a sequence located right downstream of the T7 promoter core sequence. Here the efficacy of NASBA was experimentally evaluated for different sequence variants of the 8-nucleotide downstream extension of the T7 promoter core sequence. The variants were ranked based on the known levels of RNA yields in in vitro transcription. It has been found that the rank of the 8-nucleotide extension of the T7 promoter core sequence can provide a rational for designing efficient NASBA primers. However, not all of 8-nucleotide downstream extensions characterized by the highest RNA yields in in vitro transcription were found to provide the most efficient production of target RNA amplicons in NASBA. It was shown that a careful evaluation of primer’s ability to form secondary structures by using DNA folding algorithms was still required to select the best candidate NASBA primers.